An exploration of the socio-cultural context in immigrant-concentrated neighborhoods with unusual rates of child maltreatment. Issue 3 (4th May 2021) - Finno-Velasquez, Megan; Villamil Grest, Carolina; Perrigo, Judith L.; White, Margaret; Hurlburt, Michael S.
ABSTRACT: Despite the field's understanding of individual and family level predictors of child maltreatment, research on neighborhood indicators of child abuse and neglect, especially in immigrant communities, is limited. This study employed a qualitative approach using semi-structured interviews to elicit perceptions of 28 key community informants to further understand the social dynamics of highly concentrated immigrant communities and their influence on child maltreatment. Thematic content analysis used coding consensus, co-occurrence, and comparison to analyze results. Findings suggest maltreatment reporting and behaviors may be related to three themes concerning the socio-cultural context of immigrant communities. Themes are cultural norms and values, fear and mistrust, and lack of knowledge and misinformation. Suggestions for neighborhood-level interventions in immigrant communities are presented.